E-COMMERCE DAN PENGELOLAAN KEUANGAN TERHADAP LABA USAHA UMKM - Fatimah, Siti; Muzakki, Kafidin (JURNAL AKUNTANSI BARELANG, 2025)
This study examines the influence of e-commerce and financial management on MSME business profits, with a focus on Simple Wholesale Bag MSMEs in Pasuruan. In recent years, ecommerce has become one of the important pillars in the growth of MSMEs in Indonesia, especially after the COVID-19 pandemic. This study uses a qualitative method with in-depth interviews with MSME owners, to explore the strategies implemented and the challenges faced. The results show that the adoption of e-commerce has a positive impact on increasing sales and profits, despite the challenges in financial management. In addition, digital marketing strategies such as live streaming and attractive promotions are the key to success in attracting customers. This study concludes that a good understanding of e-commerce and the effective use of financial management can increase business profits and business sustainability of MSMEs.